Cloud Computing Applications In Business Development - Rawat, Bhupesh; Bhandari, Rahul (Startupreneur Business Digital (SABDA Journal), 2023)
A crucial technology with significant consequences for company growth is cloud computing. This magazine examines how cloud computing is used in the context of company expansion and assesses how it affects several facets of organizational development. This study offers important insights into the advantages, difficulties, and best practices related to incorporating cloud computing in corporate development processes by completing an extensive literature review and looking at actual case studies. The research technique comprises a thorough examination of the body of knowledge regarding cloud computing and its function in organizational transformation. In order to pinpoint useful applications and results, case studies of businesses that effectively incorporated cloud computing into their operations are also looked at. The results reveal a number of significant benefits of using cloud computing for corporate growth. First off, cloud computing makes it simple for businesses to access a vast collection of computational resources, enabling them to grow their operations effectively and shorten the time it takes to market goods and services. With less upfront investment required for infrastructure and hardware, organizations may more efficiently allocate resources and concentrate on their core capabilities. Second, cloud computing's elasticity and scalability allow businesses to adapt swiftly to changing demand, assuring efficient resource use and low costs. Businesses may take advantage of market opportunities, adjust to shifting trends, and experience sustainable growth because to this agility. Additionally, better data security features including encryption, access controls, and data backup systems are provided by cloud computing. And finally, the use of cloud computing for corporate growth results in significant cost reductions.